Agribisnis Pesantren dan Pemberdayaan Ekonomi Lokal: Analisis Ekonomi dan Sosiokultural di Pondok Pesantren Darul Ulum Lampung Timur - Muhammad Ismail (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2025)
This study aims to analyze the agribusiness activities of Islamic boarding schools in East Lampung Regency, examine community perceptions of Islamic boarding school–based agribusiness development, identify the agribusiness development model, and assess its economic feasibility. The research was conducted at Darul Ulum Islamic Boarding School, located in Sumbergede Village, Sekampung Sub-district, East Lampung Regency. A descriptive analytical approach was employed to evaluate both economic and socio-cultural aspects of agribusiness development. The findings indicate that Islamic boarding schools play a significant role in influencing rural communities and therefore have strategic responsibility in strengthening local economic activities. The leadership of the kiai (head of the Islamic boarding school) is a key supporting factor in encouraging the adoption and sustainability of agribusiness initiatives. Furthermore, agribusiness production units function not only as income-generating enterprises for the Islamic boarding school but also as practical learning facilities for students to develop technical skills and entrepreneurial capacity. Overall, the study demonstrates that Islamic boarding school–based agribusiness has strong potential as an integrated model of economic empowerment and education in rural areas.